The Management Efficiency of the Sustainable Development Policy under Thailand's Energy Law: Enriching the SEM-based on the ARIMAXi model - Sutthichaimethee, Pruethsan; Ariyasajjakorn, Danupon (International Journal of Energy Economics and Policy, 2021)
The purpose of this research is to analyze the relationship of causal factors and the error correction ability of these factors, including economic growth, government policy, and environmental growth, under the energy law of Thailand. This research proposes a novel structural equation model called the “Structural Equation Model based on Autoregressive Integrated Moving Average with Observed Variables (SEM-based on the ARIMAXi model)”. The validity of this proposed model is confirmed upon testing the goodness of fit and white noise property. Upon analysis, this research reveals that the SEM-based on the ARIMAXi (1,1,1) model is composed of causal factors, where economic growth was found to be related to environmental growth with an influential impact rate of 0.76 per cent at a confidence interval of 99 per cent. The relationship between economic growth and government policy was also detected to have a 0.51 per cent impact at a confidence interval of 99 per cent. Furthermore, this research identifies government policy as being related to environmental growth with an impact of 0.19 per cent at a confidence interval of 99 per cent. In addition, this research indicates that economic growth is the strongest factor with an error correction ability of -0.74, followed by government policy and environmental growth factors with an error correction ability of -0.45 and -0.06, respectively. With the weakest error correction ability in environmental growth, this suggests that the government must intervene in taking action to preserve the environment. Keywords: Structural Equation Model, greenhouse gases, carrying capacity, energy consumption, Error Correction Mechanism, causal factors. JEL Classifications: P28, Q42, Q43, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.9995